SYNTHESIS OF BIODIESEL ON A HYBRID CATALYTIC-PLASMA REACTOR OVER K2O/CaO-ZnO CATALYST - Luqman Buchori; Istadi Istadi; Purwanto Purwanto (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This paper aimed to study the synergistic effects of dielectric barrier discharge plasma and 5 % K2O/CaO-ZnO catalyst on biodiesel synthesis. The catalyst was prepared using co-precipitation followed by impregnation method. The catalyst was characterized by XRD, while the catalyst basicity was tested by titration method. The effects of voltage, weight hourly space velocity (WHSV), and catalyst pellet diameter on the yield of fatty acid methyl ester (FAME) and biodiesel were studied. The transesterification process within and without plasma environment was investigated to find synergistic effect between the role of high energetic electrons from the plasma through the catalytic reaction zone and the role of basicity in the catalyst. From the results, an applied voltage of 5 kV, a WHSV of 1.186 min-1, and a catalyst diameter of 5 mm gave the better FAME yield of 77.19 %. The reaction time required was only 1.25 minutes at a discharge power of 530 W. This result proved that the plasma environment has a significant effect on performance of the hybrid catalytic-plasma reactor for biodiesel production.